Performance analysis of solar cogeneration system with different integration strategies for potable water and domestic hot water production. (15th May 2016) - Uday Kumar, N.T.; Mohan, Gowtham; Martin, Andrew
Graphical abstract: Highlights: Solar driven cogeneration system integrating membrane distillation technology is developed. System utilizes solar thermal energy for the operations without auxiliary heaters. Three different system integrations are experimentally investigated in UAE. Economical benefits of solar cogeneration system is also reported. Abstract: A novel solar thermal cogeneration system featuring the provision of potable water with membrane distillation in combination with domestic hot water supply has been developed and experimentally analyzed. The system integrates evacuated tube collectors, thermal storage, membrane distillation unit, and heat exchangers with the overall goals of maximizing the two outputs while minimizing costs for the given design conditions. Experiments were conducted during one month's operation at AURAK's facility in UAE, with average peak global irradiation levels of 650 W/m 2 . System performance was determined for three integration strategies, all utilizing brackish water (typical conductivity of 20, 000 μs/cm) as a feedstock: Thermal store integration (TSI), which resembles a conventional indirect solar domestic hot water system; Direct solar integration (DSI) connecting collectors directly to the membrane distillation unit without thermal storage; and Direct solar with thermal store integration (DSTSI), a combination of these two approaches. The DSTSI strategy offered the best performance given its operational flexibility. Here the maximum distillate productivity was 43 L/day for a total gross solar collector area of 96 m 2 . In terms of simultaneous hot water production, 277 kWh/day was achieved with this configuration. An economic analysis shows that the DSTSI strategy has a payback period of 3.9 years with net cumulative savings of 325, 000 during the 20 year system lifetime.